The Effect of Using Charts on Students’ English Speaking and Writing Ability - Nurjayanti, Nurjayanti; Ririen , Deci (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
The research problem of the study was how the implementation of using chart in teaching speaking and writing, while the objective of the study was to find out the significant effect of using chart on students’ English speaking and writing ability. The study used a quasi-experimental design with pre-test and post-test. The participants of the study were 70 students. The data were analyzed using independent sample t-test and paired sample t-test. Eta square formula also used to find an indication of the magnitude of the differences between the groups. Based on the data processing, the finding showed that there was a significant effect of using a chart on students’ English speaking and writing ability. The research finding showed that conducting the treatment by using a chart gives a significant effect 89% on the students’ speaking ability and 92% on the students’ writing ability. Based on the result of the research, it can be concluded that using a chart is one of the ways which can be used by educators to improve students’ speaking and writing skills.